Introduction of a Framework for Dynamic Knowledge Representation of the Control Structure of Transplant Immunology: Employing the Power of Abstraction with a Solid Organ Transplant Agent-Based Model - An, Gary (Frontiers in Immunology, 2015)
Agent-based modeling has been used to characterize the nested control loops and nonlinear dynamics associated with inflammatory and immune responses, particularly as a means of visualizing putative mechanistic hypotheses. This process is termed dynamic knowledge representation and serves a critical role in facilitating the ability to test and potentially falsify hypotheses in the current data- and hypothesis-rich biomedical research environment. Importantly, dynamic computational modeling aids in identifying useful abstractions, a fundamental scientific principle that pervades the physical sciences. Recognizing the critical scientific role of abstraction provides an intellectual and methodological counterweight to the tendency in biology to emphasize comprehensive description as the primary manifestation of biological knowledge. Transplant immunology represents yet another example of the challenge of identifying sufficient understanding of the inflammatory/immune response in order to develop and refine clinically effective interventions. Advances in immunosuppressive therapies have greatly improved solid organ transplant outcomes, most notably by reducing and treating acute rejection. The end goal of these transplant immune strategies is to facilitate effective control of the balance between regulatory T cells and the effector/cytotoxic T cell populations in order to generate, and ideally maintain, a tolerant phenotype. Characterizing the dynamics of immune cell populations, and the interactive feedback loops that lead to graft rejection or tolerance, is extremely challenging, but is necessary if rational modulation to induce transplant tolerance is to be accomplished. Herein is presented the Solid Organ Agent-based Model (SOTABM) as an initial example of an agent-based model that abstractly reproduces the cellular and molecular components of the immune response to solid organ transplant. Despite its abstract nature, the SOTABM is able to qualitatively reproduce acute rejection and the suppression of acute rejection by immunosuppression to generate transplant tolerance. The SOTABM is intended as an initial example of how agent-based models can be used to dynamically represent mechanistic knowledge concerning transplant immunology in a scalable and expandable form, and can thus potentially serve as useful adjuncts to the investigation and development of control strategies to induce transplant tolerance.